ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENERIMAAN KAS PADA UKM BENGKEL ALADIN SENDURO - Joanne Intania Rut Simunapendi; Hwihanus Hwihanus (Universitas 45 Surabaya, 2023)
This study aims to analyze aaccounting information systems related to sales and cash receipts at UKM Bengkel Aladin. The research method used in this thesis is descriptive. UKM Bengkel Aladin is the main object in this study. Primary data obtained from interviews with business owners. The assessment was carried out through a qualitative approach. The results of the evaluation of sales and cash receipts accounting systems and procedures at UKM Bengkel Aladin still need to be improved.